Room temperature synthesis of rutile TiO2 hierarchical nanoneedle flower morphology for dye sensitized solar cell - Hyam, Rajeshkumar S.; Bhosale, Reshma K.; Lee, Wonjoo; Han, Sung-Hwan; Hannoyer, Beatrice; Ogale, Satishchandra B. (Journal of Nanoscience and Nanotechnology, 2010)
Rutile TiO2 nanoneedle flowers (representing concurrent nano-micro hierarchical morphology) with high shape anisotropy ratio are synthesized at room temperature by using a simple and efficient one step electrochemical process of anodic dissolution. This process employs highly acidic bath of perchloric acid (pH < 2) and a large current density on the surface of Titanium foil to form nanostructures. The diameter and length of rutile TiO2 nanoneedle is similar to 8 nm and 100 nm respectively (aspect ratio > 10). Dye sensitized solar cell (DSSC) configured using such rutile TiO2 flowers is shown to exhibit IPCE of 30% and power conversion efficiency of similar to 3.6%.
Keywords: Anodization; DSSC; Nanoneedles; Rutile TiO2

Chlorate ion mediated rutile to anatase reverse phase transformation in the TiO2 nanosystem - Bhosale, Reshma; Hyam, Rajeshkumar S.; Dhanya, P.; Ogale, Satishchandra B. (Dalton Transactions, 2011)
Rutile TiO2 nanoneedles (8 nm x 100 nm) synthesized at room temperature by anodization in perchloric acid (pH < 1) are shown to undergo an interesting reverse phase transformation to anatase nanoparticles (8 nm) at 300 degrees C only if the chlorate ions are maintained in the ambient medium. When chlorate ions are removed by multiple washing, the rutile phase and the needle morphology are maintained. The mechanism of formation of the ion-stabilized solid and its thermal evolution is discussed.